Call up the (cognitive) reserves: how adult socialisation and education influences cognition in the UK Biobank - Benjamin Tari; Morgane Künzi; Vanessa Raymont (Frontiers in Psychology)
IntroductionDementia involves the loss of memory and degradation of cognitive function. Crucially, the onset of dementia may be prevented by identifying and modifying relevant risk factors years before disease onset in midlife. Commonly described modifiable risk factors include social isolation and educational attainment. Here, we aim to understand the relationships between adult activities and their effects on cognition related to mid-life aging in terms of where and how people live.MethodsWe analysed data from the UK Biobank (N = 502,165, Mage = 56.53, SDage = 8.09, 54.40% female). In particular, our path analysis investigated the associations between years of education in childhood, education later in life, social activities in adulthood, built environment (i.e., coastal distance and percentage of greenspace), socioeconomic status (i.e., Townsend deprivation index), and cognitive functions (i.e., memory, executive function, and abstract reasoning).ResultsAdult education and social activities predict better cognition. Being deprived predicts attendance in adult education classes, but fewer social activities and poorer cognition. Moreover, living in areas with less greenspace and being further away from coastlines predict attendance in adult education classes; however, only greenspace predicts participation in social activities. Finally, less greenspace and further coastal distance support abstract reasoning, whereas further coastal distance predicts poorer executive function.ConclusionWe demonstrate the potential utility of adult education and social activities which may offset the detrimental effects of deprivation. Accordingly, we argue for improved access to adult social programs in deprived/underserviced areas in the United Kingdom.